Problem solving process and creative thinking of students in ecosystem issue - Santi, Delinta Herlia; Prayitno, Baskoro Adi; Muzzazinah, M. (University of Muhammadiyah Malang, 2019)
Nowadays environmental issues challenge the educational field to cultivate problem solving process and creative thinking skills in students. The objective of this research was to observe the problem solving process and creative thinking of students at State Senior High School in Klaten Regency in solving the ecosystem problem based on the academic ability (high, medium, and low). This research was qualitative which used think-aloud technique in which the subjects (S) were nine students chosen by using stratified random sampling technique. The data analysis used was triangulation. The problem solving process skill was scored from the students? thinking structure in tackling the problem served. Furthermore, the students? creative thinking ability was measured from the students? final results in coping ecosystem problem which then was scored based on the creative thinking skill rubric. The results showed that there were errors found in problem solving process of S1, S2, S3, S4, S5, S6, S8 and S9 due to their lack of background knowledge. Meanwhile, the errors resulted by S7 were caused of misconception. In addition, the students who had high, medium, and low academic abilities tended to have the creative qualifications as creative, medium, and less creative in sequence.